Priming of possessive constructions in German: a matter of preference effects? - Schimke, Sarah; Pappert, Sandra (Languages, 2024)
We investigated structural priming in adult native speakers, focusing on possessive constructions in German, where the two alternative structures involved differ in frequency. According to error-based learning approaches to priming, the less frequent structure should lead to a larger prediction error and larger priming effects than the more frequent structure. In a comparison of preferences during a pretest and preferences during priming, we did not find evidence of such an inverse preference effect. Moreover, during priming, we observed increasing production rates of the preferred structure, hence, a cumulative priming effect. In line with hybrid models of priming, we propose that two mechanisms, namely, a mechanism learning from input as well as a mechanism accumulating activation during comprehension and production, are involved in the temporal development of priming effects. Moreover, we suggest that the interaction of the two mechanisms may depend on prior experience with the alternative structures.
Gesehen am 19.08.2024